Respostas bioquímicas e fisiológicas de Cucumis sativus e Avena sativa ao estresse causado por alumínio - Pereira, Luciane Belmonte (2010)
Aluminum (Al) is the most abundant metal in the Earth's crust, affecting growth and development of plants. The aim of this study was to investigate the effects of Al on seedlings of cucumber (Cucumis sativus L.) and oat (Avena sativa L) through the analysis of biochemical and physiological parameters. Three different genotypes of oat seedlings were studied, namely UFRGS 930598 Al-sensitive, UFRGS 17 Altolerant, and 280 Al-intermediate (resulting from the crossing UFRGS 930598 and UFRGS 17), exposed to 0, 5, 10, 20, and 30 mg/L Al. The biochemical parameters analyzed for cucumber were: the activity of antioxidant enzymes (catalase (CAT), ascorbate peroxidase (APX) and superoxide dismutase (SOD)), the levels of lipid peroxidation, leakage electrolytes, protein oxidation, and chlorophyll content. The increase of electrolyte leakage and the production of hydrogen peroxide observed are related to the decreased efficiency of the antioxidant system at the highest concentrations of Al. The antioxidant system was unable to prevent the toxicity resulting in negative effects such as lipid peroxidation, protein oxidation, and decreased plant growth. Oat seedlings were exposed to Al in different growth media. The first exposure was in the midst of semi-solid growth agar for 5 days, seedlings with five days of development and then to a hydroponic solution for 7 days with 10 days of seedling development. The content of hydrogen peroxide, lipid peroxidation, ascorbic acid and non-protein thiols (NPSH), as well as the activity of the enzymes CAT, APX and SOD, and the content of Al accumulated in the seedlings were evaluated. Enzymes activities of the antioxidant SOD and CAT were increased in UFRGS 17 and UFRGS 280 genotypes. Even when these two genotypes accumulated high concentrations of Al, they did not show high levels of lipid peroxidation and contents of hydrogen peroxide when compared with the 930598 genotype. For this genotype, an activation of the enzyme APX was observed, however, high levels of Al accumulated in the plant caused an increase in the lipid peroxidation and hydrogen peroxide content. The UFRGS 930598 genotype was more sensitive to Al than the UFRGS 17 and UFRGS 280 genotypes, which confirms the previous morphological analysis obtained by FEDERIZZI et al., 2000. Although there was increased activity of APX in this genotype, the antioxidant system was not efficient in the removal of reactive oxygen species (ROS). In order to better understand these results, a growth medium with a hydroponic solution was used in which the mobility of the metal was greater for an exposure period of 7 days with oat seedlings with 10 days of development. Besides the biochemical parameters mentioned above, the analysis of the growth of roots and shoots, fresh and dry matter, chlorophyll content, activity of the enzyme δ -aminolevulinic acid dehydratase (δ -ALA -D), and the monitoring of the pH of the hydroponic solution of each genotype were performed. The pH of the hydroponic solution of salt-tolerant genotype (UFRGS 17) showed a significant increase in pH, while the sensitive (UFRGS 930598) and intermediate (UFRGS 280) genotypes showed no significant changes. The sensitive genotype presented inhibition of root and shoot growth at the highest concentrations of Al while the tolerant and intermediate genotype showed no significant changes. The activity of antioxidant enzymes was increased after 7 days of exposure to Al in the sensitive genotype, whereas in the tolerant genotype there was no increase in this activity. In seedlings of the intermediate genotype there was an increase in the activity of CAT, APX and SOD enzymes only at higher Al concentrations (20 and 30 mg/L). Results showed that the intermediate and tolerant genotypes showed similar effects not only on the activity of enzymes of the antioxidant system, but also on the physiological parameters such as growth of roots and shoots. Even when accumulating high concentrations of Al, the intermediate genotype did not show a decrease in growth, which shows that it has resistance mechanisms related to the internal immobilization of this metal in the vacuoles. The tolerant genotype also introduces mechanisms of resistance to Al, but these mechanisms may be the exclusion of Al by binding this metal to organic acids. In order to investigate if the antioxidant system is activated in different genotypes of oat, seedlings were placed in growth medium with a hydroponic solution and withdrawn from the medium after 12, 24, and 36 h of exposure to 20 mg/L. Tolerant and intermediate genotypes showed an increase of the enzyme activity of the antioxidant system after 12 h of exposure to Al, while the sensitive genotype presented this increase only after 24 or 36 h. This difference in the rate of activation of the antioxidant system may be crucial in maintaining cellular redox homeostasis of this genotype. At this stage of development, the tolerant and the intermediate genotypes showed a stimulation of root growth while the sensitive type showed significant growth retardation. In order to compare plant species, cucumber was placed in hydroponic growth medium with the oat seedlings (sensitive and tolerant genotypes.) When cucumber was placed in hydroponic solution exposed to 20 mg/L Al along with the tolerant (UFRGS 17) and the sensitive (UFRGS 930 598) genotypes, it showed similarities with the sensitive genotype (increased catalase activity after 36 h of exposure to Al). The levels of lipid peroxidation were high after 12, 24, and 36h of exposure to Al and as a consequence there was a reduction in root growth. Considering the evaluation with tolerant (UFRGS 17) and sensitive (UFRGS 930 598) oat genotypes, the cucumber may be considered an Al-sensitive species.